Men and women who want epistemic certainty are at-risk for hostility towards women leaders. Issue 5 (3rd September 2022) - Baldner, Conrad; Pierro, Antonio; Di Santo, Daniela; Kruglanski, Arie W.
ABSTRACT: Researchers have spent the past five decades asking why women leaders face disproportionally more disapproval than their men colleagues. We extend recent research by investigating the need for cognitive closure (NCC), or the desire for stable and certain knowledge, to help answer this question. Consistent with Role Congruity Theory, we propose that individuals with this need are more likely to disapprove of women who break traditional gender roles as well as women leaders, a subcategory of nontraditional woman. We studied the NCC effect relative to the effects of gender and political orientation (i.e., women and political liberals are less likely to disapprove of women leaders). In four studies, including state and dispositional treatments of NCC and a brief meta-analyses, we argue that NCC has an indirect effect on negative attitudes toward women leaders through hostile sexism, among both men and women and from both sides of the political spectrum.